Coated tool
The small-diameter tool is coated with AlCr nitride or carbonitride rich in AlCr nitride by sputtering to reduce particles and improve durability, which solves the problems of increased particles and insufficient wear resistance caused by arc ion plating, and achieves the same durability and wear resistance as the arc ion plating method.
Patent Information
- Application Number
- CN202380061688.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-29
- Filing Date
- 2023-08-17
- Publication Date
- 2025-04-04
AI Technical Summary
In small-diameter tools, Al-rich AlCr nitride particles coated by arc ion plating can easily increase, resulting in room for improvement in the durability of the tool, and hard films that use sputtering alone may have poor wear resistance.
AlCr nitride or carbon nitride rich in AlCr is used by sputtering to reduce particles and control the crystal orientation to achieve the same durability as the arc ion plating method.
It realizes reducing particles in small-diameter tools, improving the durability of the tools, and maintaining wear resistance of the above-mentioned arc ion plating method.
Smart Images

Figure CN119768243A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a covering tool applied to a tool such as a metal mold or a cutting tool.
[0002] This application claims priority based on patent application No. 2022-135969 filed in Japan on August 29, 2022, and its contents are incorporated herein. Background Art
[0003] AlCr nitride is a film type with excellent wear resistance and heat resistance, and is widely used as a coated metal mold or a coated cutting tool. In recent years, a coated tool formed by coating AlCr nitride containing more than 70 atomic % of Al and rich in Al by arc ion plating has been proposed (Patent Documents 1 to 3).
[0004] Patent Document 1: Japanese Patent Publication No. 2016-032861
[0005] Patent Document 2: Japanese Patent Publication No. 2018-059146
[0006] Patent Document 3: Japanese Patent Publication No. 2020-040175
[0007] In a small-diameter tool such as one with a tool diameter of 2 mm or less, the influence of particles on tool performance tends to be large. The inventors have confirmed that the particles of AlCr nitride rich in Al tend to increase when coated by arc ion plating, and the durability of the tool has room for improvement.
[0008] By using the sputtering method for forming the hard film, particles can be reduced. However, when the hard film is formed by simply using the sputtering method, the wear resistance may be inferior to the wear resistance of the hard film formed by the arc ion plating method. Summary of the invention
[0009] In view of the above circumstances, an object of the present invention is to provide a coated tool which reduces particles of AlCr nitride or carbonitride rich in Al by applying a sputtering method and achieves durability equal to or higher than that of a case using an arc ion plating method.
[0010] A coated tool according to one aspect of the present invention comprises a substrate and a hard film on the substrate.
[0011] The hard film is a nitride or a carbonitride, wherein the nitride or the carbonitride contains 70 atomic % or more and 90 atomic % or less of Al, 10 atomic % or more and 30 atomic % or less of Cr, relative to the total amount of metal elements (including semi-metal elements) and non-metal elements, and contains 0.50 atomic % or less of argon (Ar), and the crystal structure of the hard film is composed of cubic crystals and hexagonal crystals.
[0012] Regarding the hard film, in the X-ray intensity distribution of the α-axis of the positive pole diagram related to the (111) plane of the cubic crystal, when the maximum intensity in the range of α angle 10° to 90° is IA and the minimum intensity is IB, IB is IA×0.5 or more,
[0013] In the X-ray intensity distribution on the α-axis of the positive pole figure related to the (110) plane of the hexagonal crystal, when the maximum intensity in the range of α angle 10° to 90° is Ia and the minimum intensity is Ib, Ib is not less than Ia×0.5.
[0014] It is preferred that IB is IA×0.6 or more.
[0015] According to the present invention, a coated tool having an Al-rich AlCr nitride sputtered film and excellent durability can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is an example of the X-ray intensity distribution on the α-axis of the positive pole diagram related to the (111) plane of the cubic crystal of the AlCr nitride according to Example 1.
[0017] Figure 2 This is an example of the X-ray intensity distribution of the α-axis of the positive pole diagram related to the (110) plane of the hexagonal crystal of the AlCr nitride according to Example 1.
[0018] Figure 3 This is an example of the X-ray intensity distribution of the α-axis of the positive pole diagram of the AlCr nitride according to Comparative Example 1 with respect to the (111) plane of the cubic crystal. DETAILED DESCRIPTION
[0019] The present inventors have confirmed that even if the sputtered film of AlCr nitride or carbonitride rich in Al has a cubic or hexagonal crystal structure, the durability of the tool is excellent by controlling the crystal orientation.
[0020] The coated tool of this embodiment is a coated tool having Al-rich nitride or carbonitride mainly composed of Al and Cr on the surface of the substrate. The coated tool of this embodiment can be applied to a metal mold or a cutting tool. In particular, it is preferably applied to a small-diameter end mill with a tool diameter of 5 mm or less, and further 3 mm or less.
[0021] In this embodiment, the substrate is not particularly limited. Cold working tool steel, hot working tool steel, high speed steel, cemented carbide, etc. can be appropriately used according to the application. The substrate can also be nitrided or bombarded in advance.
[0022] The hard film involved in this embodiment is a nitride or a carbonitride, and contains 70 atomic % or more and 90 atomic % or less of Al, and 10 atomic % or more and 30 atomic % or less of Cr relative to the total amount of metal (including semi-metal, the same below) elements. Nitrides or carbonitrides mainly composed of Al and Cr are film types with excellent balance between wear resistance and heat resistance, and also have excellent adhesion to the substrate. The hard film involved in this embodiment is preferably a nitride with better heat resistance.
[0023] The hard film involved in the present embodiment has an Al content of 70 atomic % or more when the metal element as a whole is set to 100 atomic %. The heat resistance is improved by increasing the Al content in the hard film. In addition, since it is easy to form an oxidation protective film on the surface of the tool and the film structure becomes fine, it is easy to suppress the wear of the hard film caused by welding. Furthermore, the Al content is preferably 75 atomic % or more. On the other hand, if the Al content is too large, the toughness of the hard film is significantly reduced. Therefore, the hard film involved in the present embodiment has an Al content of 90 atomic % or less when the metal element as a whole is set to 100 atomic %. Furthermore, the Al content is preferably 85 atomic % or less.
[0024] The hard film involved in this embodiment sets the Cr content to 10 atomic % or more when the metal element as a whole is set to 100 atomic %. As a result, it is easy to form a uniform and dense oxide protective film on the surface of the tool being processed, and it is easy to suppress tool damage. Furthermore, it is preferred to set the Cr content to 15 atomic % or more. On the other hand, if the Cr content is too large, Al is relatively reduced, and it is difficult to obtain the effect of increasing the Al content. Therefore, the hard film involved in this embodiment sets the Cr content to 30 atomic % or less when the metal element as a whole is set to 100 atomic %. Furthermore, the Cr content is preferably less than 25 atomic %.
[0025] The hard film according to the present embodiment preferably contains 90 atomic % or more of Al and Cr when the total metal element is 100 atomic %. The hard film according to the present embodiment may be a nitride or carbonitride of Al and Cr.
[0026] The content ratio of the metal element of the hard film involved in this embodiment can be measured by using an electron probe microanalyzer (EPMA) on the hard film after mirror finishing. In this case, for example, after the mirror finishing of the hard film surface, it can be obtained based on the average value obtained by analyzing 5 points in an analysis range with a diameter of about 1 μm.
[0027] The hard film involved in the present embodiment may also contain metal elements other than Al and Cr. For example, the hard film involved in the present embodiment may also contain one or more elements selected from the elements of Group 4a, Group 5a, Group 6a in the periodic table and Si, B, Y, Yb, and Cu for the purpose of improving wear resistance and heat resistance. These elements are elements that are usually contained in order to improve the film properties of the coated tool, and can be added within the range that does not significantly reduce the durability of the coated tool. However, if the content ratio of metal elements other than Al and Cr is too high, the durability of the coated tool may sometimes decrease. Therefore, in the case where the hard film involved in the present embodiment contains metal elements other than Al and Cr, the total content ratio is preferably less than 10 atomic % when the metal elements as a whole are set to 100 atomic %, and more preferably less than 5 atomic %.
[0028] The hard film involved in the present embodiment contains argon (Ar) of 0.50 atomic % or less relative to the total amount of metal elements and non-metal elements. The hard film involved in the present embodiment is a sputtered film, a sputtered hard film. Regarding particles that become defects of the hard film, the frequency of occurrence can be reduced by applying the sputtering method. On the other hand, since argon ions are used to sputter the target component in the sputtering method, the hard film coated by the sputtering method contains a lot of argon. In particular, argon is easily enriched at the grain boundary, and if the crystal grain size becomes fine particles, the argon content tends to increase. However, if the argon content increases, the bonding force between particles at the grain boundary will decrease. As in the hard film involved in the present embodiment, in a hard film with a large Al content, excessive argon may become a defect, so it is effective to make its content below a certain level. Specifically, the hard film involved in the present embodiment contains argon of 0.50 atomic % or less relative to the total amount of metal elements and non-metal elements. Furthermore, it is preferable that the content ratio of argon be set to 0.40 atomic % or less.
[0029] Furthermore, if the hard film according to the present embodiment is sputtered using a mixed gas containing a rare gas other than argon, the hard film may contain a rare gas other than argon.
[0030] In the sputtering method, if the content ratio of argon contained in the hard film is made infinitely close to 0 atomic %, the flow rate of argon will become too small, and the sputtering will be unstable. In addition, even if it is assumed that the content ratio of argon is close to 0 atomic %, it may damage the basic properties of the hard film applied to the cutting tool, such as toughness, heat resistance and wear resistance. Regarding the hard film involved in this embodiment, the lower limit of the content ratio of argon is not particularly limited, but in order to stabilize the sputtering method and ensure the basic film properties of the hard film applied to the coating tool, the content ratio of argon is preferably set to 0.02 atomic % or more. Furthermore, it is preferred to set the content ratio of argon to 0.05 atomic % or more. Furthermore, it is preferred to set the content ratio of argon to 0.10 atomic % or more.
[0031] The argon content of the hard film according to the present embodiment can be measured by using an electron probe microanalyzer (EPMA) on the hard film after mirror finishing, similarly to the measurement of the content of the metal element described above. Similar to the measurement of the content of the metal element described above, after mirror finishing, it can be obtained by analyzing 5 points in an analysis range with a diameter of about 1 μm and obtaining the average value.
[0032] As the non-metallic element of the hard film according to the present embodiment, a trace amount of argon, oxygen, and carbon may be contained in addition to nitrogen.
[0033] <Crystal structure>
[0034] The hard film involved in the present embodiment is composed of cubic crystals and hexagonal crystals. In the X-ray intensity distribution of the α-axis of the positive pole diagram of the cubic crystal (111) plane, the hard film involved in the present embodiment has a maximum intensity of IA and a minimum intensity of IB in the range of α angle 10° to 90°, and IB is IA×0.5 or more. As a result, the difference between the maximum intensity IA and the minimum intensity IB becomes smaller, and the X-ray intensity distribution of the cubic crystal (111) plane becomes uniform easily in the range of α angle 10° to 90°, and the cubic crystal (111) plane, which is the closest plane, becomes a state that is not strongly oriented in a specific direction. In addition, in the X-ray intensity distribution of the α-axis of the positive pole diagram related to the hexagonal crystal (110) plane, the hard film involved in the present embodiment has a maximum intensity of Ia and a minimum intensity of Ib in the range of α angle 10° to 90°, and Ib is Ia×0.5 or more. As a result, the difference between the maximum intensity Ia and the minimum intensity Ib becomes smaller, and the X-ray intensity distribution of the (110) plane of the hexagonal crystal becomes uniform easily within the range of α angle 10° to 90°, and the hexagonal crystal is not strongly oriented in a specific direction. It is speculated that the film damage is easily suppressed by the state that the (111) plane of the cubic crystal and the (110) plane of the hexagonal crystal are not strongly oriented in a specific direction, and the durability is improved.
[0035] IB is preferably IA×0.6 or more. Further, IB is preferably IA×0.7 or more. In the hard film according to the present embodiment, the (111) plane of the cubic crystal is preferably a crystal plane showing the maximum intensity in X-ray diffraction.
[0036] <Middle film, upper layer>
[0037] Regarding the coated tool of this embodiment, in order to further improve the adhesion of the hard film, an intermediate film may be provided between the substrate of the tool and the hard film as required. For example, a layer composed of any one of metal, nitride, carbonitride and carbide may be provided between the substrate of the tool and the hard film.
[0038] In addition, a hard film having a different component ratio or a different composition from the hard film involved in the present embodiment may be formed on the hard film involved in the present embodiment. Furthermore, the hard film involved in the present embodiment and a hard film having a different component ratio or a different composition from the hard film involved in the present embodiment may be stacked on each other.
[0039] <Particles>
[0040] In cross-sectional observation of the hard film according to the present embodiment, particles having a circle equivalent diameter of 1 μm or more are preferably present in an area of 100 μm. 2In the arc ion plating method, the "particles" in this specification are deposits on the hard film caused by molten particles of about 1 μm to several tens of μm flying out from the cathode. In the sputtering method, the "particles" in this specification are deposits on the hard film caused by metal particles of about 1 μm to several tens of μm suddenly scattered from the target.
[0041] In a hard film coated by physical vapor deposition, particles may be the main physical defects. In particular, coarse particles with a circle equivalent diameter of 1 μm or more may become the starting point of destruction inside the hard film, so by reducing the frequency of their occurrence, the toughness of the hard film can be improved. In this embodiment, in the cross-sectional observation of the hard film, particles with a circle equivalent diameter of 1 μm or more are preferably present at 1:100 μm per 100 μm. 2 More preferably, at every 100 μm 2 More preferably, at every 100 μm 2 Furthermore, it is preferred that no particles with a circle equivalent diameter of 5 μm or more are contained.
[0042] In addition, on the surface of the hard film, it is also preferred that particles with a circle equivalent diameter of 1 μm or more be present per 100 μm. 2 More preferably, the number of particles on the surface of the hard film is less than 5 per 100 μm. 2 More preferably, the number of particles on the surface of the hard film is 100 μm or less. 2 In the middle is one or less.
[0043] In order to evaluate the particles in the cross-sectional observation of the hard film, the hard film is mirror-finished, then processed by a focused ion beam method, and the mirror-finished surface is observed in multiple fields of view using a transmission electron microscope at 5,000 to 10,000 times. In addition, the number of particles on the surface of the hard film can be obtained by observing the surface of the hard film using a scanning electron microscope (SEM) or the like.
[0044] <Manufacturing method>
[0045] The coating of the hard film involved in this embodiment is preferably applied by sputtering method, which uses three or more AlCr alloy targets, and applies power to the targets in sequence. When switching the target to which power is applied, a time is set for simultaneously applying power to the target to which power application ends and the target to which power application begins. In such a sputtering method, the ionization rate of the target is maintained at a high level during the coating process, and a dense hard film can be obtained at a microscopic level, and there is a tendency to inevitably contain less argon and oxygen. In addition, it is preferred to set the furnace temperature of the sputtering device to 350°C to 500°C, set the bias voltage of the negative pressure applied to the substrate to -200V to -70V, and introduce Ar gas and N2 gas to set the furnace pressure to 0.1Pa to 0.4Pa. In addition, in the case of coating carbonitride, a small amount of carbon can be added to the target, or a part of the reaction gas can be replaced by methane gas.
[0046] The maximum power density of the power pulse is preferably 0.1 kW / cm 2 More preferably 0.3 kW / cm 2 In addition, in this composition system, if the energy of the film-forming ions is too high, the hexagonal crystals become too many. Therefore, the maximum power density of the power pulse is preferably 0.7 kW / cm 2 More preferably, it is 0.6 kW / cm 2 The duration of the power pulse applied to each target is preferably 30 milliseconds or less. In addition, the duration of simultaneous power application to both the alloy target to which power application is completed and the alloy target to which power application is started is preferably 20 microseconds or more and 100 microseconds or less.
[0047] Example 1
[0048] <Base material>
[0049] As a substrate, a double-edged ball end mill made of cemented carbide having a composition of WC (bal.)-Co (8.0 mass%)-VC (0.3 mass%)-Cr3C2 (0.5 mass%) and a hardness of 94.0 HRA (Rockwell hardness, value measured according to JIS G 0202) was prepared.
[0050] In this embodiment 1, a sputtering device capable of carrying six sputtering evaporation sources was used. Among these evaporation sources, six Al80Cr20 alloy targets (the numerical value is an atomic ratio, the same applies below) were installed in the device as evaporation sources in order to coat the hard film.
[0051] The tool as the substrate is fixed on the sample holder in the sputtering device, and the bias power supply is connected to the tool. In addition, the bias power supply is a structure that applies a negative bias voltage to the tool independently of the target. The tool rotates at two revolutions per minute and revolves through the fixing fixture and the sample holder. The distance between the tool and the target surface is 100 mm.
[0052] Ar and N2 were used as the introduction gas, and the introduction gas was introduced from a gas supply port provided in the sputtering device.
[0053] <Bombardment treatment>
[0054] First, before coating the tool with a hard coating, the tool was bombarded in the following order. The tool was heated for 30 minutes at a temperature of 400°C by a heater in the sputtering device. Then, the furnace of the sputtering device was evacuated and the pressure in the furnace was set to 5.0×10 -3 Then, Ar gas was introduced into the furnace of the sputtering device to adjust the pressure in the furnace to 0.8 Pa. Then, a DC bias voltage of -170 V was applied to the tool, and cleaning (bombardment treatment) of the tool with Ar ions was performed for more than 20 minutes.
[0055] <Hard film coating>
[0056] In the coating of this embodiment 1, the furnace temperature was set to 400°C, and Ar gas (0.2Pa) and N2 gas (0.1Pa) were introduced into the furnace of the sputtering device to set the furnace pressure to 0.3Pa. A DC bias voltage was applied to the substrate, the power applied to the target overlapped for 50 microseconds, and the discharge time per cycle of the power applied to each target was 1 millisecond. Then, the negative bias voltage applied to the substrate was set to -120V and the maximum power was set to 0.4kW / cm 2 Electricity was continuously applied to six Al80Cr20 alloy targets, and a hard film of about 3.0 μm was coated on the surface of the substrate.
[0057] Comparative Example 1 used an arc ion plating device. An Al60Cr40 alloy target was set in the device as an evaporation source. First, the tool was cleaned (bombarded) with Ar ions. Then, the pressure in the furnace of the arc ion plating device was evacuated to 5.0×10 -3 Pa or less, the furnace temperature was set to 500°C, and N2 gas was introduced to make the furnace pressure 3.2 Pa. Then, a DC bias voltage of -100 V was applied to the tool, and a current of 150 A was supplied to the Al60Cr40 alloy target, and a hard film of about 3.0 μm was coated on the surface of the tool. Comparative Example 1 is a coated cutting tool having a hard film of a composition commonly used in the market.
[0058] The film composition of the hard film was measured by wavelength dispersive electron probe microanalysis (WDS-EPMA) attached to an electron probe microanalyzer (JXA-8500F manufactured by JEOL Ltd.). The ball end mill used for property evaluation was mirror-finished, and the acceleration voltage was set to 10 kV and the irradiation current was set to 5 × 10-8 A. The introduction time was set to 10 seconds, and the analysis area was measured at 5 points within a range of 1 μm in diameter. The metal content ratio of the hard film and the content ratio of Ar in the total of metal components and non-metal components were calculated based on the average values.
[0059] The crystal structure was confirmed using an X-ray diffractometer (EMPYREA manufactured by PaNalytical Co., Ltd.) under measurement conditions of tube voltage 45 kV, tube current 40 mA, X-ray source Cukα (λ=0.15405 nm), and 2θ of 20 to 80 degrees.
[0060] The measurement conditions of the X-ray intensity distribution based on the positive pole diagram are as follows. In addition, when the normal line of the sample surface is located on the plane determined by the incident line and the diffraction line, the angle α is set to 90°. When the angle α is 90°, it becomes the center point on the positive pole diagram.
[0061] Tube: Cukα line
[0062] Output power: 45kV, 200mA
[0063] Beam: parallel method
[0064] Optical system: In-plane
[0065] Detector: D / teX Ultra250
[0066] Soller slits opening angle: 0.5deg
[0067] Entrance slit width: 1.0mm
[0068] Light receiving slit width: 1.0mm
[0069] Scanning method: Concentric circles
[0070] β scanning range: 0°~360° / 3.0° step
[0071] α scanning range: 0~90° / 3.0° step
[0072] [Table 1]
[0073]
[0074] The results of X-ray diffraction showed that Example 1 had cubic crystals and hexagonal crystals, while Comparative Example 1 had cubic crystals and did not contain hexagonal crystals.
[0075] Figure 1 An example of X-ray intensity distribution on the α-axis of the positive pole diagram of the AlCr nitride according to Example 1 with respect to the (111) plane of the cubic crystal is shown.
[0076] Figure 2 An example of X-ray intensity distribution on the α-axis of the positive pole diagram of the AlCr nitride according to Example 1 with respect to the (110) plane of the hexagonal crystal is shown.
[0077] Figure 3 An example of X-ray intensity distribution on the α-axis of the positive pole figure with respect to the (111) plane of the cubic crystal of the AlCr nitride according to Comparative Example 1 is shown.
[0078] like Figure 1 As shown, the X-ray intensity distribution of the cubic crystal (111) plane of the present embodiment 1 has a small difference between the maximum intensity and the minimum intensity in the α angle of 10° to 90°. The maximum intensity IA of the cubic crystal (111) plane of the present embodiment 1 is 171, and the minimum intensity IB is 141. IB is 0.82 times of IA, and IB is IA×0.5 or more. In addition, as Figure 2 As shown, the X-ray intensity distribution of the (110) plane of the hexagonal crystal of Example 1 also has a small difference between the maximum intensity and the minimum intensity in the α angle of 10° to 90°. The maximum intensity Ia of the (110) plane of the hexagonal crystal of Example 1 is 107, and the minimum intensity Ib is 75, Ib is 0.70 times Ia, and Ib is more than Ia×0.5.
[0079] On the other hand, Figure 3 As shown, the difference between the maximum intensity and the minimum intensity of the X-ray intensity distribution of the (111) plane of the cubic crystal in Comparative Example 1 is greater than that in Example 1. The maximum intensity IA of the (111) plane of the cubic crystal in Comparative Example 1 is 233, and the minimum intensity IB is 98, IB is 0.42 times IA, and IB is less than IA×0.5.
[0080] (Conditions) Dry machining
[0081] Tool: Double-edged carbide ball nose end mill
[0082] Model: EPDBE2010-6, ball head radius 0.5mm
[0083] Cutting method: bottom cutting
[0084] Workpiece: STAVAX (52HRC) (manufactured by Bohler Uddeholm Corporation)
[0085] Cutting depth: axial 0.03mm, radial 0.03mm
[0086] Cutting speed: 67.8m / min
[0087] Single-edge feed rate: 0.0135mm / edge
[0088] Cutting distance: 15m
[0089] Evaluation method: After cutting, the workpiece was observed using a scanning electron microscope at a magnification of 1000 times, and the width of friction between the tool and the workpiece was measured on the tool flank. The portion with the largest friction width was defined as the maximum flank wear width.
[0090] [Table 2]
[0091] Sample No. Maximum wear width of the flank (μm) This embodiment 1 10 Comparative Example 1 15
[0092] The maximum wear width of the flank of Example 1 is reduced, and the durability is superior to that of Comparative Example 1. The hard film of Example 1 contains a large amount of Al, and since the (111) planes of the cubic crystals and the (110) planes of the hexagonal crystals are not strongly oriented in a specific direction, film damage is suppressed, and it is estimated that the durability is superior to that of Comparative Example 1.
Claims
1. A coated tool comprising a substrate and a hard film on the substrate, wherein the coated tool is characterized in that: The hard film is a nitride or a carbonitride, wherein the nitride or the carbonitride contains 70 atomic % or more and 90 atomic % or less of Al, 10 atomic % or more and 30 atomic % or less of Cr, relative to the total amount of metal elements including semi-metals, and 0.50 atomic % or less of argon (Ar), relative to the total amount of metal elements and non-metal elements including semi-metals, and the crystal structure of the hard film is composed of cubic crystals and hexagonal crystals. Regarding the hard film, in the X-ray intensity distribution of the α-axis of the positive pole diagram of the cubic crystal (111) plane, when the maximum intensity in the range of α angle 10° to 90° is IA and the minimum intensity is IB, IB is IA×0.5 or more, In the X-ray intensity distribution on the α-axis of the positive pole figure of the hexagonal (110) plane, when the maximum intensity in the range of α angle 10° to 90° is Ia and the minimum intensity is Ib, Ib is not less than Ia×0.
5.
2. The coating tool according to claim 1, characterized in that: IB is IA×0.6 or more.
Citation Information
Patent Citations
Coated tool
JP2016032861A
Hard film, hard film coated member, and production method of hard film
JP2018059146A
Coated cutting tool
JP2020040175A
Neuron device, method for producing the same, and neural activity evaluating method
JP2022135969A